2022
DOI: 10.1108/jcp-01-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Interest in physical danger: does it mediate the relationship between gender and violent offending?

Abstract: Purpose The purpose of this study is to test the hypothesis that the relationship between gender and violent offending is mediated, in part, by an interest in participating in physically dangerous activities. Design/methodology/approach This study makes use of self-report data from a sample of college students and other adults that they recruited to participate in this study to test the hypothesis that having an interest in physically dangerous activities mediates, at least in part, the gender–violence assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(69 reference statements)
1
1
0
Order By: Relevance
“…Irrespective of relationship type, Warren and colleagues found that abductions perpetrated by male offenders under the age of 29 were most likely to result in fatal outcomes. This coincides with research showing an over representation of men in violent interpersonal crimes (Hoskin and Liftawi, 2022). The authors did not find any associations between fatality outcomes and the offenders’ ethnicity or arrest history.…”
Section: Resultssupporting
confidence: 90%
“…Irrespective of relationship type, Warren and colleagues found that abductions perpetrated by male offenders under the age of 29 were most likely to result in fatal outcomes. This coincides with research showing an over representation of men in violent interpersonal crimes (Hoskin and Liftawi, 2022). The authors did not find any associations between fatality outcomes and the offenders’ ethnicity or arrest history.…”
Section: Resultssupporting
confidence: 90%
“…Additionally, implicit measures could circumvent biases of self-reported motivation pertaining to faking, self-perception and social desirability which can, also, be of interest when interviewing offenders or predicting violent offences. This adds to literature using indirect measures to assess personality-relevant antisocial tendencies; for example, interest for physical danger was predictive of violent behavior (Hoskin and Liftawi, 2022) and heightened perceptions of vulnerability based on audio-less videos of women who appeared less confident and autonomous to the sample (Stewart et al , 2022).…”
Section: Discussionmentioning
confidence: 95%